Aplikasi Lucutan Plasma Corona Dalam Pengolahan Limbah Cair Kelapa Sawit - Pamungkas, Adityo; Anggraini, Ika Novia; Rosa, M. Khairul Amri; Herawati, Afriyastuti (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2020)
ABSTRACT The green revolution in the field of palm oil farming not only contributes to processed products but also produces large-capacity waste originating from its processing starting from the sterilization process, water from the clarification process, hydro cyclone (clay bath) water, and factory washing water. Palm oil mill effluent (LCPKS) contains dissolved and suspended solids in the form of colloids and oil residues with high BOD and COD. If this liquid waste is discharged directly into the water, it can pollute the environment. Some will settle, decompose slowly, consume dissolved dcxdcoxygen, cause turbidity, emit a sharp odor and can damage the aquatic ecosystem. To improve the parameters in the LCPKS so that it is feasible to flow to water bodies or the environment, an LCPKS treatment experiment test is performed by applying corona discharge with variations in voltage and length of time, then comparing the effect on parameters such as BOD, COD, pH and TDS on LCPKS before treatment and after treatment. From the treatment process using a corona discharge application with variations in voltage and time able to reduce BOD levels up to 35%, COD 36%, increase in TDS reached 71.56% and decreased pH by 4.11%.Key words: Palm oil mill effluent (LCPKS), Corona discharge application (Corona Discharge Treatment), COD, BOD, TDS, pH